2006
DOI: 10.1002/ijc.21797
|View full text |Cite
|
Sign up to set email alerts
|

4‐HPR modulates gene expression in ovarian cells

Abstract: Ovarian cancer has a high rate of recurrence and subsequent mortality following chemotherapy despite intense efforts to improve treatment outcomes. Recent trials have suggested that retinoids, especially 4-(N-hydroxyphenyl) retinamide (4-HPR), play an important role as a chemopreventive agent and are currently being used in clinical trials for ovarian cancer chemoprevention as well as treatment. This study examines the mechanism of its activity in premalignant and cancer cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…This study revealed modest responses to 4HPR, suggesting that, although there may be a role for chemoprevention with 4HPR, it likely acts through different pathways in normal, immortalized, and malignant cells. 40 This theory of varying pathways was confirmed and further elucidated by Brewer et al, 41 when they again treated IOSE and OVCA433 cells with 4HPR. DNA microarray was used to evaluate changes in gene expression.…”
Section: In Vitro Datamentioning
confidence: 69%
See 1 more Smart Citation
“…This study revealed modest responses to 4HPR, suggesting that, although there may be a role for chemoprevention with 4HPR, it likely acts through different pathways in normal, immortalized, and malignant cells. 40 This theory of varying pathways was confirmed and further elucidated by Brewer et al, 41 when they again treated IOSE and OVCA433 cells with 4HPR. DNA microarray was used to evaluate changes in gene expression.…”
Section: In Vitro Datamentioning
confidence: 69%
“…Both lines exhibited down-regulation of mutant BRCA genes. These results indicate that 4HPR may act through different mechanisms to yield a chemopreventive effect in premalignant cells and a chemotherapeutic effect in malignant cells 41. …”
mentioning
confidence: 87%
“…In certain clinical cases, synthetic retinoid derivatives may have advantages over natural ones like ATRA. Fenretinide (R) and CD437 promote apoptosis of ovarian cancer cells [23,24]. Their action is to increase the activity of caspase-3 and caspase-9 enzymes in both ATRA-sensitive (CAOV-3) and resistant (SKOV-3) cells [23,24].…”
Section: Ovarian Cancermentioning
confidence: 99%
“…Fenretinide (R) and CD437 promote apoptosis of ovarian cancer cells [23,24]. Their action is to increase the activity of caspase-3 and caspase-9 enzymes in both ATRA-sensitive (CAOV-3) and resistant (SKOV-3) cells [23,24]. In addition, 4-HPR and CD437 increase the expression of proapoptotic genes and mitochondria uncoupling protein in OVCA433 cells [23,24].…”
Section: Ovarian Cancermentioning
confidence: 99%
See 1 more Smart Citation